From Points to Insight: Gamifying Reflective Thinking in Design Education - Larsen, Oskar; Al-Farsi, Aisha (University of Science and Computer Technology, 2026)
Reflective practice in design education is often marginalized as a post-hoc evaluative task rather than conceptualized as a central creative and epistemic process. In this study, reflective practice is reconceptualized as a gamified learning framework that fosters metacognition, visual empathy, and self-awareness through interactive design strategies. The primary objective was to examine the extent to which gamification elements, including feedback cycles, progress visualization, and reward structures, enhance concept retention, reflective insight, and comprehension of design processes among 36 undergraduate graphic design students. Using a mixed-methods, design-based research approach, data were collected across three iterative learning cycles through digital activity logs, reflective journals, and semi-structured interviews. Quantitative analysis using paired-sample t-tests revealed a statistically significant 18% improvement in reflective accuracy and a 20% increase in conceptual retention (p < 0.05) following the implementation of gamified reflective activities. Platform analytics further indicated a 92% task completion rate, suggesting increased learner engagement associated with visual feedback and reward mechanisms. Qualitative thematic analysis identified three interrelated dimensions of reflective learning: emotional resonance, sensory awareness, and social connectedness, highlighting the multidimensional nature of reflection in gamified environments. Overall, the findings suggest that gamified reflection can support more active and emotionally engaging learning processes, positioning reflective practice as a form of “learning through play” and offering a pedagogical framework to enhance empathy, self-awareness, and reflective thinking in visual design education.